Moderation of Physical Activity between Cardiometabolic Risk and Adiponectin in Adolescents - Tadiotto, Maiara Cristina; Corazza, Patricia Ribeiro Paes; Menezes Junior, Francisco Jose de; Moraes Junior, Frederico Bento de; Lopes, Maria de Fátima Aguiar; Tozo, Tatiana Aparecida Affornali; Purim, Kátia Sheylla Malta; Mota, Jorge; Leite, Neiva (International Journal of Sports Medicine, 2023)
The aims of the study were to examine the moderating role of physical activity in the relationship between cardiometabolic risk factors and adiponectin concentration in adolescents. This is a cross-sectional study conducted with 96 adolescents of both sexes, between 11 and 17 years old. Body mass, height, fat mass (FM), fat-free mass, systolic blood pressure, diastolic blood pressure, high density lipoprotein, low density lipoprotein (LDL-c), triglycerides, insulin, adiponectin, C-reactive protein, and level of physical activity (energy expenditure questionnaire) were measured. Body mass index (BMI), triponderal mass index (TMI), homeostasis model to assessment insulin resistance (HOMA-IR), and quantitative insulin sensitivity check index (QUICKI) were calculated. Macro-PROCESS for SPSS was used for moderation analyses. Direct interactions were found for BMI, TMI, FM, insulin, and HOMA-IR and inverse for LDL-c, and QUICKI. Protection against cardiometabolic risk was found when the PA-coeff was completed above 1.57 coeff (BMI), 1.62 coeff (TMI), 1.55 coeff (FM), 1.41 coeff (LDL-c)1.60 coeff (insulin), 1.59 coeff (HOMA-IR) and 1.35 coeff (QUICKI). We conclude that physical activity was a moderator in the relationship with adiposity, insulin resistance and sensitivity, LDL-c, and adiponectin. In this context, we evidenced a relevant clinical impact on the health of adolescents, demonstrating the interaction between anthropometrics variables and physical activity.
Keywords: adiponectin; adiposity; risk factors; physical activity